Development of Operational Application System at PT. XYZ with Flask Overriding - Hattu, Aryudha; Susetyo, Yeremia (International Journal Software Engineering and Computer Science (IJSECS), 2024)
Advances in information technology have become a critical factor in increasing company operational efficiency. PT.XYZ, a business entity in the retail sector, faces an urgent need to design an operational application system that can adapt to current business dynamics. This research discusses and applies the development of operational application systems at PT.XYZ uses the Flask Overriding concept in the Flask framework. Flask Overriding is an idea in object-based programming that allows changing or replacing existing behavior in a system. This study explores the potential for implementing Flask Overriding to increase PT functionality, adaptability, and flexibility. PT XYZ operational application systems. Implementing this concept involves an in-depth analysis of a company's specific business needs, application architecture design, and practical implementation using Flask as the main framework. This research produces an operating system application head office application that is useful for assisting PT XYZ in storing and sending non-physical products needed by PT XYZ branches and head office so that the business processes and dissemination of information required for PT XYZ and its branches become efficient, fast, and structured.